The dark side of BrdU in neural stem cell biology: detrimental effects on cell cycle, differentiation and survival - Lehner, Bernadette; Sandner, Beatrice; Marschallinger, Julia; Lehner, Christine; Furtner, Tanja; Couillard-Despres, Sebastien; Rivera, Francisco J.; Brockhoff, Gero; Bauer, Hans-Christian; Weidner, Norbert; Aigner, Ludwig (Cell & tissue research, 2011)
5-Bromo-2′-deoxyuridin (BrdU) is frequently used in anaylsis of neural stem cell biology, in particular to label and to fate-map dividing cells. However, up to now, only a few studies have addressed the question as to whether BrdU labeling per se affects the cells to be investigated. Here, we focused on the potential impact of BrdU on neurosphere cultures derived from the adult rat brain and on proliferation of progenitors in vivo. In vitro, neurospheres were pulsed for 48 h with BrdU, and cell proliferation, cell cycle, differentiation, survival and adhesion properties were subsequently analyzed. BrdU inhibited the expansion of neural progenitors as assessed by MTS assay and increased the fraction of cells in the G0/G1-phase of the cell cycle. Moreover, BrdU increased cell death and dose-dependently induced adherence of NPCs. Cell adherence was accompanied by a reduced amount of active matrix-metalloproteinase-2 (MMP-2). Furthermore, BrdU repressed neuronal and oligodendroglial differentiation, whereas astroglial fate was not affected. In contrast to the in vitro situation, BrdU apparently did not influence endogenous proliferation of NPCs or neurogenesis in concentrations that are typically used for labeling of neural progenitors in vivo. Our results reveal so far uncharacterized effects of BrdU on adult NPCs. We conclude that, because of its ubiquitous use in stem cell biology, any potential effect of BrdU of NPCs has to be scrutinized prior to interpretation of data.